Short-range interactions between fibrocytes and CD8+ T cells in COPD bronchial inflammatory response - Eyraud, Edmée; Maurat, Elise; Sac-Epée, Jean-Marc; Henrot, Pauline; Zysman, Maeva; Esteves, Pauline; Trian, Thomas; Dupuy, Jean-William; Leipold, Alexander; Saliba, Antoine-Emmanuel; Begueret, Hugues; Girodet, Pierre-Olivier; et al. (eLife, 2023)
Bronchi of chronic obstructive pulmonary disease (COPD) are the site of extensive cell infiltration, allowing persistent contact between resident cells and immune cells. Tissue fibrocytes interaction with CD8 + T cells and its consequences were investigated using a combination of in situ , in vitro experiments and mathematical modeling. We show that fibrocytes and CD8 + T cells are found in the vicinity of distal airways and that potential interactions are more frequent in tissues from COPD patients compared to those of control subjects. Increased proximity and clusterization between CD8 + T cells and fibrocytes are associated with altered lung function. Tissular CD8 + T cells from COPD patients promote fibrocyte chemotaxis via the CXCL8-CXCR1/2 axis. Live imaging shows that CD8 + T cells establish short-term interactions with fibrocytes, that trigger CD8 + T cell proliferation in a CD54- and CD86-dependent manner, pro-inflammatory cytokines production, CD8 + T cell cytotoxic activity against bronchial epithelial cells and fibrocyte immunomodulatory properties. We defined a computational model describing these intercellular interactions and calibrated the parameters based on our experimental measurements. We show the model’s ability to reproduce histological ex vivo characteristics, and observe an important contribution of fibrocyte-mediated CD8 + T cell proliferation in COPD development. Using the model to test therapeutic scenarios, we predict a recovery time of several years, and the failure of targeting chemotaxis or interacting processes. Altogether, our study reveals that local interactions between fibrocytes and CD8 + T cells could jeopardize the balance between protective immunity and chronic inflammation in the bronchi of COPD patients.